Development of a Smoking Prevention Promotion Model of Secondary School Students in Nakhon Ratcha sima Province - จึงสมเจตไพศาล, ภัทรพล; ทวยมีฤทธิ์ , สันติ (Journal of Health Science of Thailand, 2021)
This action research aimed to study the smoking situation and to develop a model for smoking prevention among secondary school students as well as to evaluate the model in Nakhon Ratchasima Province. The samples in the research were divided into 4 groups as follows: (1) 117 secondary school students in 3 schools purposively selected based on the different school size, (2) 9 teachers in the selected schools, (3) 12 student parents, and (4) 9 public health officers. Research tools consist of document analysis, questionnaires, group discussions, and in-depth interviews. The quantitative data analysis with descriptive statistics consisted of frequency, percentage, mean and standard deviation. qualitative data analysis was performed through classifying and grouping the data. The finding revealed that all 3 schools had continued to operate smoke-free school project, and most students had high level of knowledge on cigarette smoking harm (Mean=4.17; SD=0.75). The attitude toward antismoking was also at a high level (Mean=4.15; SD=.67). To promote and prevent smoking among secondary school students, specific group activities such as buddy matching, motivation to reduce and quit smoking were recommended. Based on the finding, a smoking prevention promotion model of secondary school students’ self-development was developed to include: (1) relevant knowledge enhancement, (2) role-playing skill development, and (3) evaluation of the operating model. This so-called SKIN model (strength, knowledge, importance and networking) could be quite practical, appropriate, and could be used in the context of Nakhon Ratchasima and other similar provinces. Such model should be implemented continuously to prevent smoking in school students.